2013
DOI: 10.1097/01.ehx.0000425981.52914.ca
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effect of aspartame versus stevioside on the cerebellar cortex of the adult albino rat

Abstract: IntroductionSweeteners have evolved rapidly over the last 20 years and are added to a wide variety of food items, drinks, drugs, and hygiene products. Aspartame is the most frequently used artificial sweetener. In contrast, stevioside is a sweet herb that seemed to be a promising natural candidate to replace artificial sweeteners but was found to have hazardous effects on the male reproductive system. ObjectivesThe aim of this work was to compare between the histological changes in the cerebellar cortex of adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
(46 reference statements)
5
7
1
Order By: Relevance
“…However, the immunoreaction was faint on treating the rats with both ASP & OM3. These results go in agreement with those of some researchers (Olney et al, 1996;Mohamed, 2013) who stated that aspartate might stimulate the cerebral nerve cells until death. Aspartic acid is the precursor for some amino acids as glutamate, glutamine and asparagine (Humphries et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, the immunoreaction was faint on treating the rats with both ASP & OM3. These results go in agreement with those of some researchers (Olney et al, 1996;Mohamed, 2013) who stated that aspartate might stimulate the cerebral nerve cells until death. Aspartic acid is the precursor for some amino acids as glutamate, glutamine and asparagine (Humphries et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…However, these findings are inconsistent with those of earlier scholars (Lapierre et al, 1990;Tollefson and Barnard, 1992;Brace et al, 1997;Spiers et al, 1998;Mohamed, 2013) who reported that ASP-induced neuronal degeneration could provoke proliferation and infiltration of the astrocytes.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Although ASP is widely used all over the world in many products, however there was lack of awareness among consumers about its potential toxic effects (25) . Several experimental researches have confirmed the negative effects of ASP consumption on different tissues and organs such as kidney (8) , liver (14,26) , cerebral cortex (27) and salivary glands (28,29) .…”
Section: Discussionmentioning
confidence: 99%